Porous polyimide film, separator for secondary battery, and secondary battery
By adjusting the average flatness of the holes and the coefficient of variation close to the distance between holes, the problem of the film strength and breathability decrease when the hole rate is increased is solved, and high tensile fracture strength and excellent breathability are achieved, which is suitable for secondary battery separators.
Patent Information
- Application Number
- CN202010487292.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-06-01
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-06-01
AI Technical Summary
When the hole rate is increased, the existing porous polyimide films are prone to decrease the film strength or the air permeability, making it difficult to take into account both high tensile fracture strength and excellent air permeability.
By adjusting the average flatness of the holes and the coefficient of variation close to the distance between holes, it is ensured that the average flatness is in the range of 0.1 to 0.7, and the coefficient of variation close to the distance between holes is in the range of 0.10 to 0.40, forming a structure in which the surface and the back surface communicate through a plurality of holes.
It realizes the high tensile fracture strength and excellent breathability of the porous polyimide film, and is suitable for the separator application of secondary batteries.
Smart Images

Figure CN113054322B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a porous polyimide film, a separator for a secondary battery and a secondary battery. Background Art
[0002] Polyimide resin is a material having excellent properties such as mechanical strength, chemical stability, and heat resistance, and polyimide films having these properties have attracted attention.
[0003] In particular, porous polyimide films are sometimes used for applications in secondary batteries (separators for lithium-ion secondary batteries, holders for solid electrolytes in all-solid batteries, and the like).
[0004] For example, Patent Document 1 describes a secondary battery separator composed of a porous polyimide resin film having a porosity of 60% or more, a three-dimensional ordered arrangement of holes, and interconnected holes through interconnected pores.
[0005] Patent Document 2 discloses a porous film based on a polyimide resin, which has a plurality of holes whose distance in the plane direction is longer than that in the thickness direction, and the plurality of holes are connected to form a state where the front and back surfaces are connected.
[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-060539
[0007] Patent Document 2: Japanese Patent Application Publication No. 2017-128691
[0008] In a porous polyimide film, depending on the shape of the pores (specifically, the flatness), the coefficient of variation of the distance between adjacent pores, and the like, a high porosity may cause a decrease in film strength or a decrease in air permeability.
[0009] Specifically, for example, in the case of a porous polyimide membrane with circular holes and orderly arranged holes, the membrane strength may decrease. Also, in the case of a porous polyimide membrane with flat holes and an excessively large coefficient of variation of the distance between close holes, the air permeability may decrease. Summary of the invention
[0010] The object of the present invention is to provide a porous polyimide membrane having excellent tensile strength at break and air permeability compared with a case where the average flatness is less than 0.1 and the coefficient of variation of the distance between holes is less than 0.10, or a case where the average flatness is greater than 0.1 and less than 0.7 and the coefficient of variation of the distance between holes exceeds 0.40.
[0011] The above problems are solved by the following solution.
[0012] <1>
[0013] A porous polyimide film has a plurality of holes, wherein the average flattening rate of the plurality of holes is in the range of 0.1 to 0.7, the coefficient of variation of the distance between the holes is in the range of 0.10 to 0.40, and the surface and the back are connected through the plurality of holes.
[0014] <2>
[0015] according to <1> The porous polyimide membrane, wherein the average flatness is in the range of 0.2 to 0.7.
[0016] <3>
[0017] according to <1> The porous polyimide membrane has a porosity ranging from 45% to 85%.
[0018] <4>
[0019] according to <1> The porous polyimide membrane, wherein the average major diameter of the plurality of holes is in the range of 50 nm to 1500 nm.
[0020] <5>
[0021] according to <1> The porous polyimide membrane has a tensile strength of 20 MPa or more.
[0022] <6>
[0023] according to <1> to <5> The porous polyimide membrane according to any one of the preceding claims, wherein the air permeability is 300 sec / 100 mL or less.
[0024] <7>
[0025] A separator for a secondary battery, comprising <6> The porous polyimide membrane is composed of.
[0026] <8>
[0027] A secondary battery comprising <7> The secondary battery separator.
[0028] Effects of the Invention
[0029] According to this <1> , <2> , <5> or <6> The invention involved can provide a porous polyimide membrane having excellent tensile strength at break and air permeability compared to a case where the average flatness is less than 0.1 and the coefficient of variation of the distance between holes is less than 0.10, or a case where the average flatness is greater than 0.1 and less than 0.7 and the coefficient of variation of the distance between holes exceeds 0.40.
[0030] according to <3> The present invention can provide a porous polyimide film having excellent tensile strength at break and air permeability compared with a case where the porosity is less than 40% or exceeds 90%.
[0031] according to <4> The present invention can provide a porous polyimide film having excellent tensile strength at break and air permeability compared with a case where the average major diameter of a plurality of pores is less than 50 nm or exceeds 1500 nm.
[0032] according to <7> The invention involved can provide a separator for lithium ion secondary batteries having excellent tensile strength at break and cycle characteristics compared to a porous polyimide membrane having an average flatness of less than 0.1 and a coefficient of variation of the distance between holes of less than 0.10, or an average flatness of greater than 0.1 and less than 0.7 and a coefficient of variation of the distance between holes exceeding 0.40.
[0033] according to <8> The invention involved provides a secondary battery having excellent tensile strength and cycle characteristics compared to a lithium ion secondary battery separator having a porous polyimide membrane having an average flatness of less than 0.1 and a coefficient of variation of the distance between holes of less than 0.10, or an average flatness of greater than 0.1 and less than 0.7 and a coefficient of variation of the distance between holes exceeding 0.40. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Embodiments of the present invention will be described in detail with reference to the following drawings.
[0035] Figure 1 is a schematic diagram showing an example of a cross section of a porous polyimide membrane according to the present embodiment;
[0036] Figure 2A is a schematic diagram for explaining the proximity of a cavity and the distance between the proximity cavities;
[0037] Figure 2B is a schematic diagram for explaining the proximity of a cavity and the distance between the proximity cavities;
[0038] Figure 3 is a partial cross-sectional schematic diagram showing an example of a lithium ion secondary battery;
[0039] Figure 4 is a partial cross-sectional schematic diagram showing an example of an all-solid-state battery;
[0040] Figure 5 is a cross-sectional photograph of the porous polyimide membrane of Example 2;
[0041] Figure 6 This is a cross-sectional photograph of the porous polyimide membrane of Example 10. DETAILED DESCRIPTION
[0042] Hereinafter, embodiments of the present invention will be described in detail.
[0043] <Porous polyimide membrane>
[0044] The porous polyimide membrane involved in this embodiment is a porous polyimide membrane having a plurality of holes, wherein the average flatness of the holes is greater than or equal to 0.1 and less than or equal to 0.7, the coefficient of variation of the distance between the holes is greater than or equal to 0.10 and less than or equal to 0.40, and the surface and the back surface are connected through the connection of the plurality of holes.
[0045] The porous polyimide membrane according to the present embodiment has excellent tensile strength at break and air permeability by adopting the above-mentioned structure. The reason for this is not clear, but is presumed as follows.
[0046] It is considered that the average flatness of the holes in the porous polyimide film according to the present embodiment is 0.1 to 0.7 and the coefficient of variation of the distance between the holes is 0.10 to 0.40, and therefore the flat holes are arranged with appropriate disorder.
[0047] It is considered that since the holes are arranged as described above, a coarse skeleton portion based on the resin (ie, polyimide) is formed between the holes, and this coarse skeleton portion functions as a beam structure in the thickness direction of the porous polyimide film.
[0048] As a result, it is estimated that even when the porosity is high, a porous polyimide film excellent in tensile strength can be obtained.
[0049] In addition, it is presumed that since the holes are arranged as described above and the front and back surfaces are connected by a plurality of holes, the porous polyimide membrane according to the present embodiment can obtain sufficient communicating portions between the front and back surfaces, thereby increasing air permeability.
[0050] 〔Hole〕
[0051] The porous polyimide film according to the present embodiment has a plurality of holes.
[0052] The holes included in the porous polyimide film according to the present embodiment will be described with reference to the drawings.
[0053] Figure 1 It is a schematic diagram showing a cross section in the thickness direction of the porous polyimide membrane according to the present embodiment.
[0054] like Figure 1 As shown, the porous polyimide membrane 100 is composed of a skeleton portion 10 based on a resin (ie, polyimide) and a plurality of cavities 20 dispersed in the skeleton portion 10 .
[0055] Furthermore, most of the plurality of holes 20 are connected to each other so that the front surface FA and the back surface FB are in communication with each other.
[0056] [Average flatness]
[0057] The average flatness of the plurality of holes in the porous polyimide film according to the present embodiment is 0.1 or more and 0.5 or less.
[0058] From the viewpoint of improving the strength of the film, the average flatness of the plurality of holes is, for example, preferably 0.2 or more and 0.7 or less, and more preferably 0.2 or more and 0.6 or less.
[0059] [Coefficient of variation of the distance between close holes]
[0060] The coefficient of variation of the distance between proximal holes of the porous polyimide film according to the present embodiment is 0.10 or more and 0.40 or less.
[0061] From the viewpoint of improving the strength of the film, the coefficient of variation of the distance between the near holes is, for example, preferably 0.12 or more and 0.40 or less, and more preferably 0.15 or more and 0.40 or less.
[0062] Here, the flatness ratio and the distance between adjacent holes will be described with reference to the drawings.
[0063] According to the scanning electron microscope (SEM), Figure 1 The flatness and the distance between adjacent holes were determined from the values obtained by observing and measuring the cross section in the thickness direction of the porous polyimide film shown.
[0064] Furthermore, the cavities in the porous polyimide membrane are Figure 1 As shown, the holes are connected to each other, but the flatness and the distance between the holes are calculated by treating each hole as an independent hole.
[0065] For example, in Figure 2A In the case of the four holes 20a, 20b, 20c, and 20d shown in FIG. Figure 2B Four cavities 20a, 20b, 20c, and 20d are shown as being independent from the outer edges of the respective cavities.
[0066] Close to a hole means that when a straight line L is drawn from the center of a hole X to the center of a hole Y with a certain hole X as a reference, other holes Z do not touch the straight line L and the distance from the center of hole X to the center of hole Y is within 3 times of the average major diameter. The distance between close holes means the distance from the center of hole X to the center of hole Y.
[0067] Specifically, close to the hole means that Figure 2BFor example, when the hole 20c (equivalent to the hole X) is used as a reference, when a straight line (equivalent to the straight line L) is drawn from the center Oc of the hole 20c, the holes 20a, 20b, and 20d (all equivalent to the hole Y) that are in contact with the straight line are not in contact with the other holes (equivalent to the hole Z). Figure 2B In the embodiment, the cavity 20c is in contact with the cavities 20a, 20b, and 20d, but a skeleton made of resin may be present between the cavity 20c and the cavities 20a, 20b, and 20d. When a skeleton made of resin is present between the cavity 20c and the cavities 20a, 20b, and 20d, the distance from the center Oc of the cavity 20c to the centers Oa, Ob, and Od of the cavities 20a, 20b, and 20d, respectively, needs to be within 3 times of the average pore diameter.
[0068] The distance between the close holes refers to, for example, the distance between the center Oc of the hole 20c and the centers Oa, Ob, and Od of the holes 20a, 20b, and 20d, which are the close holes, respectively, when the hole 20c is used as a reference.
[0069] In addition, Figure 2B In the figure, when the hole 20a is used as a reference, the only hole close to the hole is the hole 20c, and the holes 20b and 20d are not close to the hole.
[0070] Next, observation and measurement using a scanning electron microscope (SEM) will be described in detail.
[0071] First, the porous polyimide film was cut in the thickness direction to prepare a sample for measurement with the cut surface as the measurement surface. Furthermore, the sample for measurement was observed and measured using a VE SEM manufactured by KEYENCE using standard installed image processing software. The long diameter and short diameter of the holes were measured for 100 holes in the cross section of the sample for measurement. Furthermore, the distance between the close holes was measured for the close holes at 200 positions in the cross section of the sample for measurement.
[0072] Here, the major diameter of the hole refers to the length of the long side of the circumscribed rectangle of the hole, and the minor diameter of the hole refers to the length of the short side of the circumscribed rectangle of the hole.
[0073] The flatness is calculated from the values of the major axis and the minor axis obtained by the above measurement by the following formula (I). The average value of the flatness of 100 holes is defined as the “average flatness” in this embodiment.
[0074] Formula (I) Flatness = (long diameter - short diameter) / long diameter
[0075] Furthermore, the coefficient of variation of the distance between the holes is calculated based on the value of the distance between the holes obtained by the above measurement (the value at the position of n: 200) and the average value of the distance between the holes obtained based on the value. Specifically, the average value of the distance between the holes, the value of each distance between the holes (the value at the position of n: 200) and the difference (i.e., "deviation") are squared to obtain the average value of the sum of the obtained values, the positive square root of the average value is taken (i.e., "squaring 1 / 2"), and the obtained standard deviation is divided by the average value to calculate the coefficient of variation of the distance between the holes.
[0076] [Porosity]
[0077] From the viewpoint of ease of application to a secondary battery separator, the porosity of the porous polyimide film according to the present embodiment is, for example, preferably 40% to 90%, and more preferably 45% to 85%.
[0078] When the porosity is within the above range, when the porous polyimide film according to the present embodiment is applied to a secondary battery separator, there is a tendency to suppress a decrease in cycle characteristics.
[0079] Here, the porosity in the porous polyimide film is determined from the apparent density and true density of the porous polyimide film.
[0080] The apparent density d is the mass (g) of the porous polyimide film divided by the volume (cm2) of the porous polyimide film including the pores. 3 The apparent density d can also be expressed as the mass per unit area of the porous polyimide membrane (g / m 2 ) divided by the thickness (μm) of the porous polyimide film.
[0081] The true density ρ is the mass (g) of the porous polyimide membrane divided by the volume of the porous polyimide membrane minus the pores (i.e., the volume of only the skeleton based on the resin) (cm 3 ) value.
[0082] The porosity of the porous polyimide film was calculated by the following formula (II).
[0083] Formula (II) Porosity (%) = {1-(d / ρ)}×100 = [1-{(w / t) / ρ)}]×100
[0084] d: Apparent density of porous polyimide membrane (g / cm 3 )
[0085] ρ: True density of porous polyimide membrane (g / cm 3 )
[0086] w: mass per unit area of porous polyimide membrane (g / m 2 )
[0087] t: thickness of porous polyimide membrane (μm)
[0088] [Average major diameter]
[0089] From the perspective of applicability to secondary battery separators (more specifically, suppression of lithium dendrites in lithium-ion secondary batteries when suitable for secondary battery separators), the porous polyimide membrane involved in this embodiment has an average major diameter of a plurality of holes of, for example, preferably greater than 50 nm and less than 1500 nm, and more preferably greater than 50 nm and less than 1000 nm.
[0090] Here, the average major diameter of the plurality of holes is defined as the average value of the major diameters of 100 holes observed and measured in a cross section in the thickness direction of the porous polyimide film using the above-described scanning electron microscope (SEM).
[0091] [Tensile breaking strength]
[0092] The tensile strength at break of the porous polyimide film according to the present embodiment is, for example, preferably 20 MPa or more, more preferably 25 MPa or more, and further preferably 30 MPa or more.
[0093] In particular, for example, it is preferable to achieve the above-mentioned tensile strength at break in a porous polyimide film having a porosity within a range of 50% to 85%.
[0094] When the tensile strength at break is within the above range, when the porous polyimide membrane according to the present embodiment is applied to a secondary battery separator, excellent mechanical strength tends to be obtained.
[0095] Here, the tensile breaking strength is measured in the following manner.
[0096] First, a strip-shaped measurement sample having a width of 5 mm, a length of 100 mm, and a thickness of 100 μm was prepared.
[0097] A long strip of test specimen was stretched under the following conditions using STROGRAPH VE-1D (Toyo Seiki Seisaku-sho, Ltd.), and the tensile breaking strength was determined from the stress (load / cross-sectional area) at the time of breaking of the test specimen.
[0098] Distance between chucks: 50mm
[0099] ·Stretching speed: 500mm / min
[0100] Temperature: 23℃
[0101] Relative humidity: 55%
[0102] [Breathability]
[0103] The air permeability of the porous polyimide membrane according to the present embodiment is, for example, preferably 300 sec / 100 mL or less, more preferably 270 sec / 100 mL or less, and further preferably 250 sec / 100 mL or less.
[0104] When the porous polyimide membrane according to the present embodiment is applied to a secondary battery separator, by setting the air permeability within the above range, there is a tendency to suppress a decrease in cycle characteristics.
[0105] The air permeability of the porous polyimide film according to the present embodiment is measured by the air permeability test method according to the Gurley method (JIS P 8117: 2009).
[0106] 〔Resin-based skeleton〕
[0107] The porous polyimide membrane according to the present embodiment has a skeleton portion composed of polyimide.
[0108] The polyimide contained in the resin-based skeleton portion is not particularly limited. In addition, the resin-based skeleton portion may contain other components in addition to the polyimide within a range that does not impair the excellent effects of tensile strength at break and air permeability.
[0109] As other components, other additives contained in the polyimide precursor solution mentioned later are mentioned.
[0110] [Average film thickness]
[0111] The average film thickness of the porous polyimide film according to the present embodiment is not particularly limited and can be selected according to the intended use.
[0112] The average film thickness of the porous polyimide film may be, for example, 10 μm or more and 1000 μm or less. The average film thickness of the porous polyimide film may be 20 μm or more, or 30 μm or more. Furthermore, the average film thickness of the porous polyimide film may be 500 μm or less, or 400 μm or less.
[0113] Here, the average film thickness of the porous polyimide film is obtained by observing 10 locations in the cross section in the thickness direction using a scanning electron microscope (SEM), measuring the film thickness at each observation location based on 10 SEM images, and averaging the 10 measured values (film thickness) obtained.
[0114] <Method for producing porous polyimide membrane>
[0115] Hereinafter, a method for producing the porous polyimide membrane according to the present embodiment will be described.
[0116] The porous polyimide membrane according to the present embodiment is preferably produced through, for example, the following steps.
[0117] That is, there can be cited a process of applying a polyimide precursor solution containing a polyimide precursor, resin particles and a solvent on a substrate to form a coating film, then drying the coating film to form a coating film containing the polyimide precursor and the resin particles (hereinafter also referred to as the first process), a process of removing the particles from the coating film (hereinafter also referred to as the second process), and a process of heating the coating film to imidize the polyimide precursor in the coating film (hereinafter also referred to as the third process).
[0118] Hereinafter, each step will be described.
[0119] [1st step]
[0120] In the first step, a polyimide precursor solution containing a polyimide precursor, resin particles, and a solvent is applied onto a substrate to form a coating film, and then the coating film is dried to form a coating film containing the polyimide precursor and the resin particles.
[0121] [Polyimide precursor solution]
[0122] (Polyimide Precursor)
[0123] The polyimide precursor solution used in the first step contains a polyimide precursor.
[0124] The polyimide precursor is preferably a resin having a repeating unit represented by the general formula (I), for example.
[0125] [Chemical formula 1]
[0126]
[0127] (In the general formula (I), A represents a tetravalent organic group, and B represents a divalent organic group.)
[0128] Here, in the general formula (I), the tetravalent organic group represented by A is a residue obtained by removing four carboxyl groups from tetracarboxylic dianhydride serving as a raw material.
[0129] On the other hand, the divalent organic group represented by B is a residue obtained by removing two amino groups from a diamine compound serving as a raw material.
[0130] That is, the polyimide precursor having a repeating unit represented by the general formula (I) is a polymer of a tetracarboxylic dianhydride and a diamine compound.
[0131] As the tetracarboxylic dianhydride, any of aromatic and aliphatic compounds may be mentioned, and aromatic compounds are preferred. That is, in the general formula (I), the tetravalent organic group represented by A is preferably an aromatic organic group.
[0132] Examples of the aromatic tetracarboxylic dianhydride include pyromellitic acid dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-biphenyl sulfone tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, 3,3',4,4'-dimethyldiphenylsilane tetracarboxylic dianhydride, 3,3',4,4'-tetraphenylsilane tetracarboxylic dianhydride, 1,2,3,4-furan tetracarboxylic dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenyl sulfide dianhydride, 4,4'-bis(3 ,4-dicarboxyphenoxy)diphenylsulfone dianhydride, 4,4'-bis(3,4-dicarboxyphenoxy)diphenylpropane dianhydride, 3,3',4,4'-perfluoroisopropylidene diphthalic acid dianhydride, 3,3',4,4'-biphenyltetracarboxylic acid dianhydride, 2,3,3',4'-biphenyltetracarboxylic acid dianhydride, bis(phthalic acid)phenylphosphine oxide dianhydride, p-phenylene-bis(triphenylphthalic acid) dianhydride, m-phenylene-bis(triphenylphthalic acid) dianhydride, bis(triphenylphthalic acid)-4,4'-diphenyl ether dianhydride, bis(triphenylphthalic acid)-4,4'-diphenylmethane dianhydride, and the like.
[0133] Examples of the aliphatic tetracarboxylic dianhydride include butanetetracarboxylic dianhydride, 1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,3-dimethyl-1,2,3,4-cyclobutanetetracarboxylic dianhydride, 1,2,3,4-cyclopentanetetracarboxylic dianhydride, 2,3,5-tricarboxycyclopentylacetic dianhydride, 3,5,6-tricarboxynorbornane-2-acetic dianhydride, 2,3,4,5-tetrahydrofurantetracarboxylic dianhydride, 5-(2,5-dioxotetrahydrofurfuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic dianhydride, and bicyclo[2,2,2]-oct-7-ene-2,3,5,6-tetracarboxylic dianhydride. aliphatic or alicyclic tetracarboxylic dianhydrides; aliphatic tetracarboxylic dianhydrides having an aromatic ring such as 1,3,3a,4,5,9b-hexahydro-(2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, 1,3,3a,4,5,9b-hexahydro-5-methyl-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione, and 1,3,3a,4,5,9b-hexahydro-8-methyl-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-c]furan-1,3-dione.
[0134] Among these, as tetracarboxylic dianhydrides, for example, aromatic tetracarboxylic dianhydrides are preferred, and specifically, for example, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyl ether tetracarboxylic dianhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride are preferred, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride are further preferred, and 3,3',4,4'-biphenyltetracarboxylic dianhydride is particularly preferred.
[0135] Moreover, the tetracarboxylic dianhydride may be used individually by 1 type, and may use 2 or more types together simultaneously.
[0136] When two or more kinds of tetracarboxylic acid are used in combination, aromatic tetracarboxylic acid dianhydride or aliphatic tetracarboxylic acid may be used simultaneously, or aromatic tetracarboxylic acid dianhydride and aliphatic tetracarboxylic acid dianhydride may be used in combination.
[0137] On the other hand, the diamine compound is a diamine compound having two amino groups in the molecular structure. As the diamine compound, any of aromatic and aliphatic compounds can also be cited, and aromatic compounds are preferred. That is, in the general formula (I), the divalent organic group represented by B is preferably an aromatic organic group.
[0138] Examples of the diamine compound include p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylethane, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfone, 1,5-diaminonaphthalene, 3,3-dimethyl-4,4'-diaminobiphenyl, 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, 4,4'-diaminobenzanilide, 3,5-diaminonaphthalene, 3,3-dimethyl-4,4'-diaminobiphenyl, 5-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, 6-amino-1-(4'-aminophenyl)-1,3,3-trimethylindane, 4,4'-diaminobenzanilide, 3,5 -diamino-3'-trifluoromethylbenzanilide, 3,5-diamino-4'-trifluoromethylbenzanilide, 3,4'-diaminodiphenyl ether, 2,7-diaminofluorene, 2,2-bis(4-aminophenyl)hexafluoropropane, 4,4'-methylene-bis(2-chloroaniline), 2,2',5,5'-tetrachloro-4,4'-diaminobiphenyl, 2,2'-dichloro-4,4'-diamino-5,5'-dimethoxybiphenyl, 3,3'-dimethoxy-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)-biphenyl, 1,3'-bis(4-aminophenoxy)benzene, 9,9-bis(4-aminophenyl)fluorene, 4,4'-(p-phenyleneisopropylidene)dianiline, 4,4'-(m-phenyleneisopropylidene)dianiline, 2,2'-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane, 4,4'- Aromatic diamines such as bis[4-(4-amino-2-trifluoromethyl)phenoxy]-octafluorobiphenyl; aromatic diamines having two amino groups bonded to an aromatic ring and heteroatoms other than the nitrogen atom of the amino groups such as diaminotetraphenylthiophene; 1,1-m-xylene diamine, 1,3-propane diamine, tetramethylene diamine, pentamethylene diamine, octamethylene diamine, nonamethylene diamine, 4,4-diaminoheptamethylene diamine, 1,4-diaminocyclohexane, isophorone diamine, tetrahydrodicyclopentadiene diamine, hexahydro-4,7-methylene indene dimethylene diamine, tricyclo[6,2,1,0 2.7 ]-undecylidene dimethyl diamine, 4,4'-methylenebis(cyclohexylamine) and other aliphatic diamines and alicyclic diamines.
[0139] Among these, the diamine compound is preferably an aromatic diamine compound, and specifically, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl sulfide, and 4,4'-diaminodiphenyl sulfone are preferred, and 4,4'-diaminodiphenyl ether and p-phenylenediamine are particularly preferred.
[0140] The diamine compound may be used alone or in combination of two or more. When two or more are used in combination, an aromatic diamine compound or an aliphatic diamine compound may be used separately or in combination of an aromatic diamine compound and an aliphatic diamine compound.
[0141] The weight average molecular weight of the polyimide precursor used in the present embodiment is, for example, preferably 5,000 or more and 300,000 or less, and more preferably 10,000 or more and 150,000 or less.
[0142] The weight average molecular weight of the polyimide precursor was measured by gel permeation chromatography (GPC) under the following measurement conditions.
[0143] ·Column: TOSOH TSKgelα-M (7.8mm ID×30cm)
[0144] ·Eluent: DMF (dimethylformamide) / 30mM LiBr / 60mM phosphoric acid
[0145] Flow rate: 0.6mL / min
[0146] Injection volume: 60μL
[0147] Detector: RI (differential refractive index detector)
[0148] In the present embodiment, the content of the polyimide precursor is, for example, preferably 0.1 mass % to 40 mass %, and preferably 1 mass % to 25 mass %, based on the total mass of the polyimide precursor solution.
[0149] (particle)
[0150] The polyimide precursor solution used in the first step contains particles.
[0151] From the viewpoint of forming holes, for example, it is preferred that the particles are dispersed in the polyimide precursor solution without being dissolved.
[0152] In addition, the material of the particles is not particularly limited as long as the particles are insoluble in the polyimide precursor solution.
[0153] Here, in the present embodiment, “the particles are insoluble” includes not only the case where the particles are insoluble in the target liquid (specifically, the solvent contained in the polyimide precursor solution) at 25° C., but also the case where the particles are soluble in the target liquid within a range of 3 mass % or less.
[0154] Particles are roughly classified into resin particles and inorganic particles, and any of these can be used. However, from the viewpoint of excellent removability of particles in the second step described later, resin particles are preferred, for example.
[0155] (resin particles)
[0156] The resin particles are not particularly limited as long as they are insoluble in the polyimide precursor solution (specifically, the solvent contained in the polyimide precursor solution). In consideration of the removability of particles in the second step described below, resin particles composed of a resin other than polyimide are preferred.
[0157] Examples of the resin particles include resin particles obtained by polycondensation of polymerizable monomers such as polyester resins and urethane resins, and resin particles obtained by addition polymerization (specifically, radical addition polymerization) of polymerizable monomers such as vinyl resins, olefin resins, and fluororesins.
[0158] Among these, the resin particles are preferably vinyl resins, for example, and specifically, at least one selected from the group consisting of (meth)acrylic resins, (meth)acrylate resins, styrene / (meth)acrylic resins, and polystyrene resins.
[0159] Furthermore, the resin particles may be cross-linked or not.
[0160] Furthermore, from the viewpoint of simplifying the process of producing the polyimide precursor solution, the resin particles are preferably used as a resin particle dispersion containing the resin particles obtained by, for example, emulsion polymerization.
[0161] Here, in the present embodiment, "(meth)acrylic acid" has a meaning including both "acrylic acid" and "methacrylic acid".
[0162] When the resin particles are composed of a vinyl resin, examples of monomers for obtaining the vinyl resin include the following monomers.
[0163] Examples of monomers for obtaining vinyl resins include styrenes having a styrene skeleton, such as styrene, alkyl-substituted styrenes (e.g., α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), halogen-substituted styrenes (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), and vinylnaphthalene; esters having a vinyl group (also referred to as (meth)acrylates), such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, lauryl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; vinyl nitriles such as acrylonitrile and methacrylonitrile; vinyl ethers such as vinyl methyl ether and vinyl isobutyl ether; vinyl ketones such as vinyl methyl ketone, vinyl ethyl ketone, and vinyl isopropenyl ketone; acids such as (meth)acrylic acid, maleic acid, cinnamic acid, fumaric acid, and vinyl sulfonic acid; and bases such as ethyleneimine, vinylpyridine, and vinylamine.
[0164] In addition to the above monomers, monofunctional monomers such as vinyl acetate, difunctional monomers such as ethylene glycol dimethacrylate, nonane diacrylate, and decanediol diacrylate, and polyfunctional monomers such as trimethylolpropane triacrylate and trimethylolpropane trimethacrylate may be used together as other monomers.
[0165] Furthermore, the vinyl resin may be a resin using these monomers alone or a resin using a copolymer of two or more monomers.
[0166] When the resin particles are composed of a vinyl resin, for example, a vinyl resin obtained using styrene as a monomer is preferred. As the vinyl resin obtained using styrene, the proportion of styrene in all monomer components is, for example, preferably 20% by mass or more and 100% by mass or less, and more preferably 40% by mass or more and 100% by mass or less.
[0167] That is, the vinyl resin preferably contains 20% by mass or more and 100% by mass or less, and more preferably 40% by mass or more and 100% by mass or less, of structural units derived from styrene based on the mass of the vinyl resin.
[0168] The average particle size, shape, etc. of the resin particles are not particularly limited and may be appropriately determined according to the size and / or shape of the target voids.
[0169] The volume average particle size of the resin particles may be, for example, in the range of 0.05 μm or more and 3.0 μm or less. The volume average particle size of the resin particles may be, for example, preferably 0.07 μm or more, preferably 0.09 μm or more, and more preferably 0.10 μm or more. Furthermore, the volume average particle size of the resin particles may be, for example, preferably 2.50 μm or less, preferably 2.45 μm or less, and more preferably 2.40 μm or less.
[0170] As for the average particle size of the resin particles, the particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (for example, COULTER counter LS13, Beckman Coulter) is used. For the divided particle size range (channel), a cumulative distribution is drawn for the volume from the small particle size side, and the cumulative particle size that is 50% relative to all particles is measured as the volume average particle size D50v.
[0171] (Inorganic particles)
[0172] As inorganic particles, for example, specifically, inorganic particles such as silica particles, magnesium oxide particles, aluminum oxide particles, zirconium oxide particles, calcium carbonate particles, calcium oxide particles, titanium dioxide particles, zinc oxide particles, and cerium oxide particles can be cited. As described above, the shape of the particles is preferably, for example, particles that are close to spherical. In this viewpoint, as inorganic particles, for example, inorganic particles of silica particles, magnesium oxide particles, calcium carbonate particles, magnesium oxide particles, and aluminum oxide particles are preferred, and inorganic particles of silica particles, titanium oxide particles, and aluminum oxide particles are more preferred, and silica particles are further preferred.
[0173] These inorganic particles may be used alone or in combination of two or more.
[0174] When the wettability and dispersibility of the inorganic particles to the solvent of the polyimide precursor solution are insufficient, the surface of the inorganic particles may be modified as necessary.
[0175] Examples of methods for modifying the surface of inorganic particles include a method of treating with an alkoxysilane having an organic group such as a silane coupling agent, and a method of coating with an organic acid such as oxalic acid, citric acid, and lactic acid.
[0176] The average particle size and shape of the inorganic particles are not particularly limited and may be appropriately determined according to the size and shape of the target cavities.
[0177] The content of the particles contained in the polyimide precursor solution used in the first step is preferably, for example, 0.1 mass % to 40 mass % or less, preferably 0.5 mass % to 30 mass % or less, more preferably 1 mass % to 25 mass % or less, and further preferably 1 mass % to 20 mass % or less, relative to the total mass of the polyimide precursor solution.
[0178] (Solvent)
[0179] The polyimide precursor solution used in the first step contains a solvent.
[0180] For example, the solvent is preferably a solvent that dissolves the polyimide precursor and does not dissolve or hardly dissolves the particles.
[0181] The solvent is not particularly limited as long as it has the above-mentioned properties, but is preferably a water-soluble organic solvent, water, and a mixed solvent thereof, and more preferably a mixed solvent of a water-soluble organic solvent and water (also referred to as an aqueous solvent).
[0182] -Water-soluble organic solvents-
[0183] The term "water-soluble" in the water-soluble organic solvent means that the target substance is dissolved in water at 1 mass % or more at 25°C.
[0184] Examples of the water-soluble organic solvent include aprotic polar solvents, water-soluble ether solvents, water-soluble ketone solvents, and water-soluble alcohol solvents.
[0185] Specifically, examples of aprotic polar solvents include N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-1,3-dimethyl-2-imidazolidinone (DMI), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide (DEAc), dimethyl sulfoxide (DMSO), hexamethylenephosphoric triamide (HMPA), N-methylcaprolactam, N-acetyl-2-pyrrolidone, 1,3-dimethyl-imidazolidinone, etc. Among these, preferred aprotic polar solvents include acetyl N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-1,3-dimethyl-2-imidazolidinone (DMI), and N,N-dimethylacetamide (DMAc).
[0186] The water-soluble ether solvent is a water-soluble solvent having an ether bond in one molecule. Examples of the water-soluble ether solvent include tetrahydrofuran (THF), dioxane, trioxane, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, and diethylene glycol diethyl ether. Among these, tetrahydrofuran and dioxane are preferred as water-soluble ether solvents.
[0187] The water-soluble ketone solvent is a water-soluble solvent having a ketone group in one molecule. Examples of the water-soluble ketone solvent include acetone, methyl ethyl ketone, cyclohexanone, etc. Among these, acetone is preferred as the water-soluble ketone solvent.
[0188] The water-soluble alcohol solvent is a water-soluble solvent having an alcoholic hydroxyl group in one molecule. Examples of the water-soluble alcohol solvent include methanol, ethanol, 1-propanol, 2-propanol, tert-butyl alcohol, ethylene glycol, monoalkyl ethers of ethylene glycol, propylene glycol, monoalkyl ethers of propylene glycol, diethylene glycol, monoalkyl ethers of diethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butylene glycol, 1,4-butylene glycol, 2,3-butylene glycol, 1,5-pentanediol, 2-butene-1,4-diol, 2-methyl-2,4-pentanediol, glycerol, 2-ethyl-2-hydroxymethyl-1,3-propanediol, 1,2,6-hexanetriol, and the like. Among these, preferred water-soluble alcohol solvents include methanol, ethanol, 2-propanol, ethylene glycol, monoalkyl ethers of ethylene glycol, propylene glycol, monoalkyl ethers of propylene glycol, diethylene glycol, and monoalkyl ethers of diethylene glycol.
[0189] For example, it is preferable to contain an organic amine compound as the water-soluble organic solvent.
[0190] Hereinafter, the organic amine compound will be described.
[0191] Organic amine compounds
[0192] The organic amine compound is a compound that makes the polyimide precursor (its carboxyl group) amine salt to improve its solubility in aqueous solvents and also functions as an imidization accelerator. Specifically, the organic amine compound is preferably an amine compound with a molecular weight of 170 or less. The organic amine compound is preferably a compound other than a diamine compound that is a raw material of the polyimide precursor.
[0193] The organic amine compound is preferably a water-soluble compound, for example. Water-soluble means that the target substance dissolves in water at 1% by mass or more at 25°C.
[0194] Examples of the organic amine compound include primary amine compounds, secondary amine compounds and tertiary amine compounds.
[0195] Among these, as the organic amine compound, at least one selected from secondary amine compounds and tertiary amine compounds (especially tertiary amine compounds) is preferred. If a tertiary amine compound or a secondary amine compound is used as the organic amine compound (especially a tertiary amine compound), the solubility of the polyimide precursor in the solvent is easily increased, the film forming property is easily improved, and the storage stability of the polyimide precursor solution is easily improved.
[0196] Furthermore, as the organic amine compound, in addition to monovalent amine compounds, divalent or higher polyvalent amine compounds can be mentioned. If a divalent or higher polyvalent amine compound is used, a pseudo-crosslinked structure is easily formed between molecules of the polyimide precursor, and the storage stability of the polyimide precursor solution is easily improved.
[0197] Examples of the primary amine compound include methylamine, ethylamine, n-propylamine, isopropylamine, 2-ethanolamine, and 2-amino-2-methyl-1-propanol.
[0198] Examples of the secondary amine compound include dimethylamine, 2-(methylamino)ethanol, 2-(ethylamino)ethanol, and morpholine.
[0199] Examples of the tertiary amine compound include 2-dimethylaminoethanol, 2-diethylaminoethanol, 2-dimethylaminopropanol, pyridine, triethylamine, picoline, N-methylmorpholine, N-ethylmorpholine, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, and N-alkylpiperidines (e.g., N-methylpiperidine, N-ethylpiperidine, etc.).
[0200] From the viewpoint of obtaining a film with high strength, the organic amine compound is preferably a tertiary amine compound, for example. From this viewpoint, at least one selected from the group consisting of 2-dimethylaminoethanol, 2-diethylaminoethanol, 2-dimethylaminopropanol, pyridine, triethylamine, picoline, N-methylmorpholine, N-ethylmorpholine, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, N-methylpiperidine, and N-ethylpiperidine is further preferred. In particular, N-alkylmorpholine is preferably used.
[0201] Here, as the organic amine compound, from the viewpoint of obtaining a film with high strength, for example, an amine compound having an aliphatic cyclic structure or an aromatic cyclic structure containing a nitrogen heterocyclic structure (hereinafter referred to as a "nitrogen-containing heterocyclic amine compound") is also preferred. As the nitrogen-containing heterocyclic amine compound, a tertiary amine compound is more preferred. That is, a cyclic tertiary amine compound is more preferred.
[0202] Examples of the cyclic tertiary amine compound include isoquinolines (amine compounds having an isoquinoline skeleton), pyridines (amine compounds having a pyridine skeleton), pyrimidines (amine compounds having a pyrimidine skeleton), pyrazines (amine compounds having a pyrazine skeleton), piperazines (amine compounds having a piperazine skeleton), triazines (amine compounds having a triazine skeleton), imidazoles (amine compounds having an imidazole skeleton), morpholines (amine compounds having a morpholine skeleton), polyaniline, polypyridine, and the like.
[0203] As the cyclic tertiary amine compound, from the viewpoint of obtaining a polyimide film with suppressed film thickness deviation, for example, at least one selected from the group consisting of morpholines, pyridines, piperidines, and imidazoles is preferred, and morpholines (amine compounds having a morpholine skeleton) (i.e., morpholine compounds) are more preferred. Among these, at least one selected from the group consisting of N-methylmorpholine, N-methylpiperidine, pyridine, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, and picoline is more preferred, and N-methylmorpholine is more preferred.
[0204] The organic amine compound may be used alone or in combination of two or more.
[0205] The content ratio of the organic amine compound used in this embodiment is preferably 30% or less, and more preferably 15% or less relative to the total mass of the polyimide precursor solution. The lower limit of the content ratio of the organic amine compound is not particularly limited, and for example, it can be 1% or more relative to the total mass of the polyimide precursor solution.
[0206] The water-soluble organic solvent may be used alone or in combination of two or more.
[0207] In addition, from the viewpoint of suppressing the residue in the porous polyimide membrane and obtaining a porous polyimide membrane with high mechanical strength, the boiling point of the water-soluble organic solvent is preferably 270°C or lower, more preferably 60°C or higher and 250°C or lower, and further preferably 80°C or higher and 230°C or lower.
[0208] The content ratio of the water-soluble organic solvent used in the present embodiment is, for example, preferably 30 mass % or less, and more preferably 20 mass % or less, relative to the total mass of the aqueous solvent contained in the polyimide precursor solution.
[0209] In addition, the lower limit of the content ratio of the water-soluble organic solvent is not particularly limited, and for example, it may be 1% or more relative to the total mass of the polyimide precursor solution.
[0210] -water-
[0211] Examples of water include distilled water, ion-exchanged water, ultrafiltered water, and pure water.
[0212] The content of water used in the present embodiment is, for example, preferably 50 mass % to 90 mass % inclusive, more preferably 60 mass % to 90 mass % inclusive, and further preferably 60 mass % to 80 mass % inclusive, relative to the total mass of the aqueous solvent contained in the polyimide precursor solution.
[0213] The content of the aqueous solvent contained in the polyimide precursor solution used in the first step is, for example, preferably 50 mass % or more and 99 mass % or less, and preferably 40 mass % or more and 99 mass % or less, based on the total mass of the polyimide precursor solution.
[0214] (Other additives)
[0215] The polyimide precursor solution used in the first step may contain a catalyst for promoting the imidization reaction, a leveling agent for improving the film formation quality, and the like.
[0216] As the catalyst for accelerating the imidization reaction, a dehydrating agent such as acid anhydride, an acid catalyst such as a phenol derivative, a sulfonic acid derivative, a benzoic acid derivative, etc. can be used.
[0217] Furthermore, depending on the purpose of use of the polyimide film, for example, in order to impart conductivity, the polyimide precursor solution may contain a conductive agent (for example, a conductive agent having a volume resistivity of less than 10 7 Ω·cm conductive agent) or semi-conductive agent (for example, a conductive agent with a volume resistivity of 10 7 Ω·cm or more and 10 13 Ω·cm or less conductive agent).
[0218] Conductive agents include, for example, carbon black (e.g., acidic carbon black at pH 5.0 or less); metals (e.g., aluminum, nickel, etc.); metal oxides (e.g., yttrium oxide, tin oxide, etc.); ion conductive substances (e.g., potassium titanate, LiCl, etc.); and the like.
[0219] These conductive agents may be used alone or in combination of two or more.
[0220] Furthermore, the polyimide precursor solution may contain inorganic particles added to improve the mechanical strength depending on the intended use of the polyimide film.
[0221] Examples of the inorganic particles include particulate materials such as silica powder, alumina powder, barium sulfate powder, titanium oxide powder, mica, and talc.
[0222] Furthermore, LiCoO2, LiMn2O, etc. used as electrodes of lithium ion batteries may also be included.
[0223] [Method for preparing polyimide precursor solution]
[0224] The method for preparing the polyimide precursor solution used in the first step is not particularly limited.
[0225] From the viewpoint of simplifying the process, for example, a method of preparing a polyimide precursor solution by synthesizing a polyimide precursor in a dispersion obtained by dispersing particles in an aqueous solvent is preferred. In addition, when the particles are resin particles, the dispersion can be obtained by granulating the resin particles in an aqueous solvent.
[0226] Specifically, the following method can be mentioned as an example of the preparation method of a polyimide precursor solution.
[0227] First, resin particles are granulated in an aqueous solvent to obtain a resin particle dispersion, and then, in the resin particle dispersion, tetracarboxylic dianhydride and a diamine compound are polymerized in the presence of an organic amine compound to generate a resin (polyimide precursor) to prepare a polyimide precursor solution.
[0228] Another example of the method for preparing the polyimide precursor solution includes a method of mixing a solution obtained by dissolving a polyimide precursor in an aqueous solvent with dried resin particles, a method of mixing a solution obtained by dissolving a polyimide precursor in an aqueous solvent with a dispersion obtained by preliminarily dispersing resin particles in an aqueous solvent, and the like.
[0229] [Coating and Drying of Polyimide Precursor Solution]
[0230] In the first step, the polyimide precursor solution obtained by the above-described method is applied to a substrate to form a coating film. The coating film includes a solution containing a polyimide precursor and particles. Moreover, the particles in the coating film are distributed in a state where aggregation is suppressed.
[0231] Then, the coating film formed on the substrate is dried to form a coating film containing a polyimide precursor and particles.
[0232] The substrate on which the polyimide precursor solution is applied is not particularly limited.
[0233] Examples of the substrate include a substrate made of a resin such as polystyrene and polyethylene terephthalate; a substrate made of glass; a substrate made of ceramics; a metal substrate such as iron and stainless steel (SUS); and a composite material substrate in which these materials are combined.
[0234] Furthermore, the substrate may be subjected to a release treatment using a silicone or fluorine-based release agent to provide a release layer as required. It is also effective to roughen the surface of the substrate to a size approximately equal to the particle size to promote exposure of the particles on the substrate contact surface.
[0235] The method for coating the polyimide precursor solution on the substrate is not particularly limited, and examples thereof include various methods such as spray coating, spin coating, roll coating, bar coating, slot die coating, and ink jet coating.
[0236] The method for drying the coating film formed on the substrate is not particularly limited, and various methods such as heat drying, natural drying, and vacuum drying may be mentioned.
[0237] More specifically, it is preferred to form a coating by drying the coating film so that the solvent remaining in the coating film becomes 50% or less (eg, preferably 30% or less) based on the solid content of the coating film.
[0238] In addition, since the dispersion state of the particles changes depending on the drying rate, the disorder of the dispersion state of the pores in the produced porous polyimide film is controlled by the drying rate.
[0239] Specifically, if the drying speed is slowed down, the particles are easy to move in the coating film, so the dispersibility of the particles in the coating film is improved, and there is a tendency that the disorder of the dispersed state of the holes in the porous polyimide film is reduced. On the other hand, if the drying speed is accelerated, the particles are easily fixed in the coating film in an unevenly distributed state, so there is a tendency that the disorder of the dispersed state of the holes in the porous polyimide film becomes higher.
[0240] The drying speed may be controlled by adjusting the drying temperature, the drying time, and the like.
[0241] In the first step, after the coating film is obtained and then dried to form a film, a treatment for exposing particles may be performed. By performing the treatment for exposing particles, the porosity of the porous polyimide film can be increased.
[0242] Specific examples of the treatment for exposing particles include the following methods.
[0243] In the process of obtaining a coating film containing a polyimide precursor and particles and drying the coating film to form a film containing a polyimide precursor and particles, as described above, the polyimide precursor in the formed film is in a state that can be dissolved in water. Therefore, by, for example, wiping the film with water or immersing it in water, the particles can be exposed from the film. Specifically, for example, by wiping the surface of the film with water to expose the particles, the polyimide precursor (and solvent) coating the particles is removed. As a result, the particles are exposed on the surface of the treated film.
[0244] In particular, when a film in which no particles are buried is formed, it is preferable to adopt, for example, the above-mentioned treatment as a treatment for exposing the particles buried in the film.
[0245] [Second and third steps]
[0246] In the second step, particles are removed from the film obtained in the first step. By removing particles from the film, a porous film can be formed.
[0247] Then, in the third step, the film is heated to imidize the polyimide precursor in the film.
[0248] Through the second step and the third step, a porous polyimide membrane can be manufactured.
[0249] [Removal of particles]
[0250] The method for removing particles from the film in the second step may be appropriately determined according to the particles in the film.
[0251] Examples of methods for removing particles from the film include a method of removing particles (preferably resin particles) by decomposing them by heating, a method of removing particles by dissolving them with an organic solvent, and a method of removing resin particles by decomposing them with a laser or the like.
[0252] These methods may be performed alone or in combination of two or more. By using two or more methods for removing particles from the film in combination, the particle removal rate can be adjusted to control the shape of the cavities (specifically, the flattening ratio).
[0253] When a method of decomposing and removing particles by heating is used, there is also a method that is used in conjunction with the third step described later, but from the perspective of the controllability of the shape of the holes (specifically, the flatness), it is preferred to perform the third step (imidization) after removing the particles from the film through the second step.
[0254] In the second step, in the case of a method of decomposing and removing the resin particles by heating, the following conditions can be mentioned as heating conditions.
[0255] The heating temperature is, for example, preferably 150°C to 350°C, more preferably 170°C to 350°C, and further preferably 200°C to 350°C.
[0256] The heating time is, for example, preferably from 1 minute to 60 minutes, more preferably from 1 minute to 45 minutes, and even more preferably from 1 minute to 30 minutes.
[0257] When a method of removing the resin particles by dissolving with an organic solvent is used, specifically, a method of bringing the film into contact with an organic solvent to dissolve and remove the resin particles in the organic solvent is exemplified.
[0258] Examples of the method of bringing the film into contact with the organic solvent include a method of immersing the film in the organic solvent, a method of applying the organic solvent on the film, and a method of bringing the film into contact with vapor of the organic solvent.
[0259] The organic solvent used to dissolve the resin particles is not particularly limited as long as it does not dissolve the polyimide precursor and the polyimide and can dissolve the resin particles.
[0260] When the particles are resin particles, as the organic solvent, for example, ethers such as tetrahydrofuran and 1,4-dioxane; aromatics such as benzene and toluene; ketones such as acetone; and esters such as ethyl acetate are used.
[0261] Among these, ethers such as tetrahydrofuran and 1,4-dioxane; and aromatics such as benzene and toluene are preferred, and tetrahydrofuran and toluene are more preferably used.
[0262] When the method of dissolving and removing particles by organic solvent is used, it is preferably performed when the imidization ratio of the polyimide precursor in the film is 10% or more, for example, from the viewpoint of particle removability and suppression of dissolution of the film itself in the organic solvent.
[0263] As a method for making the imidization ratio 10% or more, the first step heating mentioned later is mentioned, for example.
[0264] That is, for example, it is preferred that the particles in the film be dissolved and removed using an organic solvent after the first stage heating described below.
[0265] [Imidization]
[0266] In the third step, for the heating for imidizing the polyimide precursor in the film, for example, multi-stage heating of two or more stages is preferably used.
[0267] For example, when the particles are resin particles and heating is performed in two stages, specifically, the following heating conditions are employed.
[0268] In addition, the shape of the hole (specifically, the flatness) can be controlled by the heating conditions when the polyimide precursor is imidized. By appropriately controlling the heating conditions (i.e., the heating temperature and the heating time), the shrinkage rate of the film (especially in the thickness direction) changes, so the shape of the hole (specifically, the flatness) can be controlled.
[0269] As the heating condition of the first stage, for example, a temperature that can maintain the shape of the resin particles is preferred. Specifically, for example, it is preferably in the range of 50°C or more and less than 250°C, and preferably in the range of 100°C or more and 230°C or less. And, as the heating time, for example, it is preferably in the range of 10 minutes or more and 120 minutes or less. The higher the heating temperature, the shorter the heating time can be.
[0270] In the first-stage heating conditions, the heating temperature is also referred to as a pre-imidization temperature, and the heating time is also referred to as a pre-imidization time.
[0271] As the heating conditions of the second stage, for example, heating can be performed at a temperature of 250° C. to 500° C. (for example, preferably 300° C. to 450° C.) for 20 minutes to 120 minutes. By setting the heating conditions in this range, the imidization reaction is further performed. When performing the heating reaction, it is preferred to heat the reaction in stages or gradually increase the temperature at a certain speed before reaching the final temperature of the heating.
[0272] In the heating conditions of the second step, the heating temperature is also referred to as the calcination temperature, and the heating time is also referred to as the calcination time.
[0273] The heating conditions are not limited to the two-step heating method, and a one-step heating method may be used. In the one-step heating method, for example, imidization can be completed using only the heating conditions shown in the second step.
[0274] Here, the imidization ratio of the polyimide precursor will be described.
[0275] Examples of the partially imidized polyimide precursor include precursors having a structure of a repeating unit represented by the following general formula (I-1), the following general formula (I-2), and the following general formula (I-3).
[0276] [Chemical formula 2]
[0277]
[0278] In the general formula (I-1), the general formula (I-2) and the general formula (I-3), A represents a tetravalent organic group, and B represents a divalent organic group. l represents an integer greater than 1, and m and n each independently represent an integer greater than 0 or 1.
[0279] In addition, A and B have the same meanings as A and B in the general formula (I) described later.
[0280] The imidization rate of the polyimide precursor represents the ratio of the number of imide ring-closed bonding parts (2n+m) in the bonding part (tetracarboxylic dianhydride and the reaction part with the diamine compound) of the polyimide precursor to the total number of bonding parts (2l+2m+2n). That is, the imidization rate of the polyimide precursor is represented by "(2n+m) / (2l+2m+2n)".
[0281] In addition, the imidization ratio (value of "(2n+m) / (2l+2m+2n)") of the polyimide precursor was measured by the following method.
[0282] -Measurement of Imidization Ratio of Polyimide Precursor-
[0283] Preparation of polyimide precursor samples
[0284] (i) The polyimide precursor solution to be measured is applied on a silicon wafer to a film thickness ranging from 1 μm to 10 μm to prepare a coating film sample.
[0285] (ii) The coating sample is immersed in tetrahydrofuran (THF) for 20 minutes to replace the solvent in the coating sample with tetrahydrofuran (THF). The immersion solvent is not limited to THF, and can be selected from solvents that do not dissolve the polyimide precursor and can be mixed with the solvent components contained in the polyimide precursor solution. Specifically, alcohol solvents such as methanol and ethanol, and ether compounds such as dioxane are used.
[0286] (iii) The coating sample was taken out of THF, and N2 gas was blown into the THF adhering to the surface of the coating sample to remove it. The coating sample was dried at a temperature within a range of 5°C to 25°C for 12 hours or more under a reduced pressure of 10 mmHg or less to prepare a polyimide precursor sample.
[0287] Preparation of 100% imidization standard sample
[0288] (iv) In the same manner as in the above (i), a polyimide precursor solution to be measured is applied onto a silicone wafer to prepare a coating film sample.
[0289] (v) The coating film sample was heated at 380° C. for 60 minutes to carry out an imidization reaction, thereby preparing a 100% imidization standard sample.
[0290] ·Measurement and analysis
[0291] (vi) The infrared absorption spectra of the 100% imidization standard sample and the polyimide precursor sample were measured using a Fourier transform infrared spectrophotometer (manufactured by HORIBA, Ltd., FT-730). The 1780 cm-1 wavelength of the 100% imidization standard sample was determined. -1 The absorption peak (Ab'(1780cm) derived from the imide bond near -1 ))Relative to 1500cm -1 The absorption peak (Ab'(1500cm) originating from the aromatic ring -1 )) ratio I'(100).
[0292] (vii) The polyimide precursor sample was measured in the same manner to obtain the 1780 cm -1 The absorption peak (Ab(1780cm) derived from the imide bond near -1 ))Relative to 1500cm -1 The absorption peak (Ab(1500cm) originating from the aromatic ring-1 )) of the ratio I(x).
[0293] Then, the imidization ratio of the polyimide precursor was calculated according to the following formula using the measured absorption peaks I′(100) and I(x).
[0294] Formula: Imidization ratio of polyimide precursor = I(x) / I'(100)
[0295] Formula: I'(100)=(Ab'(1780cm -1 )) / (Ab'(1500cm -1 ))
[0296] Formula: I(x)=(Ab(1780cm -1 )) / (Ab(1500cm -1 ))
[0297] The imidization rate of the polyimide precursor is also applicable to the imidization rate of the aromatic polyimide precursor. When the imidization rate of the aliphatic polyimide precursor is measured, the peak derived from the structure that does not change before and after the imidization reaction is used as the internal standard peak instead of the absorption peak of the aromatic ring.
[0298] The substrate used in the first step may be peeled off from the film after the first step, may be peeled off from the film after the second step, or may be peeled off from the obtained porous polyimide film after the third step.
[0299] <Lithium ion secondary battery separator and secondary battery>
[0300] A separator for a lithium ion secondary battery according to this embodiment and a secondary battery according to this embodiment will be described.
[0301] The separator for lithium ion secondary batteries according to the present embodiment includes the porous polyimide film according to the present embodiment described above.
[0302] Furthermore, the secondary battery according to the present embodiment includes the separator for lithium ion secondary batteries according to the present embodiment.
[0303] Below, reference Figure 3 A separator for a lithium ion secondary battery according to this embodiment and a secondary battery according to this embodiment will be described.
[0304] Figure 3 It is a partial cross-sectional schematic diagram showing an example of a lithium ion secondary battery according to the present embodiment.
[0305] like Figure 3As shown, the lithium ion secondary battery 200 includes a positive electrode active material layer 110, a separator layer 510 and a negative electrode active material layer 310 contained in an outer casing not shown. The positive electrode active material layer 110 is provided on the positive electrode collector 130, and the negative electrode active material layer 310 is provided on the negative electrode collector 330. The separator layer 510 is provided in a manner of separating the positive electrode active material layer 110 from the negative electrode active material layer 310, and the positive electrode active material layer 110 and the negative electrode active material layer 310 are arranged between the positive electrode active material layer 110 and the negative electrode active material layer 310 in a manner of facing each other. The separator layer 510 includes a separator 511 and an electrolyte 513 filled in the cavity of the separator 511. The separator 511 is suitable for the porous polyimide film involved in this embodiment. In addition, the positive electrode collector 130 and the negative electrode collector 330 are components provided as needed.
[0306] (Positive Electrode Collector 130 and Negative Electrode Collector 330)
[0307] The material used for the positive electrode current collector 130 and the negative electrode current collector 330 is not particularly limited as long as it is a known conductive material. For example, metals such as aluminum, copper, nickel, and titanium can be used.
[0308] (Positive Electrode Active Material Layer 110)
[0309] The positive electrode active material layer 110 is a layer containing a positive electrode active material. Known additives such as a conductive aid and a binder resin may be included as needed. The positive electrode active material is not particularly limited, and known positive electrode active materials may be used. For example, composite oxides containing lithium (LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiFeMnO4, LiV2O5, etc.), phosphates containing lithium (LiFePO4, LiCoPO4, LiMnPO4 and LiNiPO4, etc.), conductive polymers (polyacetylene, polyaniline, polypyrrole, polythiophene, etc.), etc. may be cited. The positive electrode active material may be used alone or in combination of two or more.
[0310] (Negative Electrode Active Material Layer 310)
[0311] The negative electrode active material layer 310 is a layer containing a negative electrode active material. Known additives such as a binder resin may be included as needed. The negative electrode active material is not particularly limited, and known negative electrode active materials can be used. For example, carbon materials (graphite (natural graphite, artificial graphite), carbon nanotubes, graphitized carbon, low-temperature calcined carbon, etc.), metals (aluminum, silicon, zirconium, titanium, etc.), metal oxides (tin dioxide, lithium titanate, etc.), etc.) may be cited. One type of negative electrode active material may be used alone, or two or more types may be used simultaneously.
[0312] (Electrolyte 513)
[0313] The electrolyte solution 513 may be, for example, a non-aqueous electrolyte solution containing an electrolyte and a non-aqueous solvent.
[0314] Examples of the electrolyte include lithium salt electrolytes (LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiN(FSO2)2, LiN(CF3SO2)2, LiN(C2F5SO2), LiC(CF3SO2)3, etc.) The electrolytes may be used alone or in combination of two or more.
[0315] As the non-aqueous solvent, cyclic carbonates (ethylene carbonate, propylene carbonate and butylene carbonate, etc.), linear carbonates (diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, etc.) etc. can be mentioned. The non-aqueous solvent can be used alone or in combination of two or more.
[0316] (Method of Manufacturing Lithium Ion Secondary Battery 200)
[0317] An example of a method for manufacturing the lithium ion secondary battery 200 will be described.
[0318] A coating liquid for forming the positive electrode active material layer 110 containing a positive electrode active material is applied to the positive electrode current collector 130 and dried to obtain a positive electrode including the positive electrode active material layer 110 provided on the positive electrode current collector 130 .
[0319] Similarly, a coating liquid for forming the negative electrode active material layer 310 containing the negative electrode active material is applied to the negative electrode current collector 330 and dried to obtain a negative electrode having the negative electrode active material layer 310 provided on the negative electrode current collector 330. The positive electrode and the negative electrode may be compressed as necessary.
[0320] Next, a separator 511 is arranged between the positive electrode active material layer 110 and the negative electrode active material layer 310 in such a manner that the positive electrode active material layer 110 of the positive electrode and the negative electrode active material layer 310 of the negative electrode are opposed to each other to obtain a laminated structure. In the laminated structure, the positive electrode (positive electrode collector 130, positive electrode active material layer 110), the separator layer 510, and the negative electrode (negative electrode active material layer 310, negative electrode collector 330) are sequentially laminated. At this time, compression processing can be performed as needed.
[0321] Next, after the stacked structure is housed in an exterior member, the electrolyte 513 is injected into the stacked structure. The injected electrolyte 513 also permeates into the pores of the separator 511.
[0322] In this way, the lithium ion secondary battery 200 is obtained.
[0323] Above, reference Figure 3 Although the lithium ion secondary battery according to the present embodiment has been described, the lithium ion secondary battery according to the present embodiment is not limited thereto. As long as the porous polyimide membrane according to the present embodiment is applied, the form thereof is not particularly limited.
[0324] <All-solid-state battery>
[0325] Next, a fully solid-state battery to which the porous polyimide membrane according to the present embodiment is applied will be described. Figure 4 Provide explanation.
[0326] Figure 4 is a partial cross-sectional schematic diagram showing an example of an all-solid-state battery according to the present embodiment. Figure 4 As shown, the all-solid-state battery 300 includes a positive electrode active material layer 220, a solid electrolyte layer 620, and a negative electrode active material layer 420 contained in an outer casing member not shown. The positive electrode active material layer 220 is provided on the positive electrode collector 240, and the negative electrode active material layer 420 is provided on the negative electrode collector 440. The solid electrolyte layer 620 is arranged between the positive electrode active material layer 220 and the negative electrode active material layer 420 in a manner that the positive electrode active material layer 220 and the negative electrode active material layer 420 are opposed to each other. The solid electrolyte layer 620 includes a solid electrolyte 624 and a retainer 622 for retaining the solid electrolyte 624, and the solid electrolyte 624 is filled in the cavity of the retainer 622. The retainer 622 for retaining the solid electrolyte 624 is applied with the porous polyimide film involved in this embodiment. In addition, the positive electrode collector 240 and the negative electrode collector 440 are components provided as needed.
[0327] (Positive Electrode Collector 240 and Negative Electrode Collector 440)
[0328] Examples of materials used for the positive electrode current collector 240 and the negative electrode current collector 440 include the same materials as those described above for the lithium ion secondary battery.
[0329] (Positive Electrode Active Material Layer 220 and Negative Electrode Active Material Layer 420)
[0330] Examples of materials used for the positive electrode active material layer 220 and the negative electrode active material layer 420 include the same materials as those described above for the lithium ion secondary battery.
[0331] (Solid Electrolyte 624)
[0332] The solid electrolyte 624 is not particularly limited, and a known solid electrolyte may be used, such as a polymer solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, a halide solid electrolyte, a nitride solid electrolyte, and the like.
[0333] As the polymer solid electrolyte, fluororesins (homopolymers such as polyvinylidene fluoride, polyhexafluoropropylene, polytetrafluoroethylene, copolymers containing them as structural units, etc.), polyethylene oxide resins, polyacrylonitrile resins, polyacrylate resins, etc. can be cited. From the viewpoint of excellent lithium ion conductivity, for example, it is preferred to contain a polymer solid electrolyte. From the same viewpoint, for example, it is preferred to contain a sulfide solid electrolyte containing sulfur and at least one of lithium and phosphorus as a constituent element.
[0334] Examples of the oxide solid electrolyte include oxide solid electrolyte particles containing lithium, such as Li2O-B2O3-P2O5 and Li2O-SiO2.
[0335] As the sulfide solid electrolyte, there can be mentioned a sulfide solid electrolyte containing sulfur and at least one of lithium and phosphorus as a constituent element. For example, there can be mentioned 8Li2O·67Li2S·25P2S5, Li2S, P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li3PO4-P2S5, LiI-Li2S-P2O5, LiI-Li2S-B2S3, etc.
[0336] Examples of the halide solid electrolyte include LiI and the like.
[0337] Examples of nitride solid electrolytes include Li3N and the like.
[0338] (Method for Manufacturing All-Solid State Battery 300)
[0339] An example of a method for manufacturing the all-solid-state battery 300 will be described.
[0340] The coating liquid for forming the positive electrode active material layer 220 containing the positive electrode active material is applied to the positive electrode current collector 240 and dried to obtain a positive electrode including the positive electrode active material layer 220 provided on the positive electrode current collector 240 .
[0341] Similarly, a coating liquid for forming the negative electrode active material layer 420 containing the negative electrode active material is applied to the negative electrode current collector 440 and dried to obtain a negative electrode including the negative electrode active material layer 420 provided on the negative electrode current collector 440 .
[0342] The positive electrode and the negative electrode can be compressed as needed.
[0343] Next, a coating liquid containing the solid electrolyte 624 for forming the solid electrolyte layer 620 is applied onto the substrate and dried to form a layered solid electrolyte.
[0344] Next, a porous polyimide film as a retainer 622 and a layered solid electrolyte 624 are stacked on the positive electrode active material layer 220 of the positive electrode as a material for forming the solid electrolyte layer 620. In addition, a negative electrode is stacked on the material for forming the solid electrolyte layer 620 so that the negative electrode active material layer 420 of the negative electrode becomes the positive electrode active material layer 220 side to form a stacked structure. In the stacked structure, the positive electrode (positive electrode collector 240, positive electrode active material layer 220), the solid electrolyte layer 620, and the negative electrode (negative electrode active material layer 420, negative electrode collector 440) are stacked in this order.
[0345] Next, the stacked structure is subjected to compression processing to impregnate the solid electrolyte 624 into the pores of the porous polyimide film as the support 622 , thereby supporting the solid electrolyte 624 .
[0346] Next, the stacked structure is housed in an exterior member.
[0347] In this way, the all-solid-state battery 300 is obtained.
[0348] Above, reference Figure 4 Although the all-solid-state battery according to the present embodiment has been described, the all-solid-state battery according to the present embodiment is not limited thereto. As long as the porous polyimide membrane according to the present embodiment is applied, the form thereof is not particularly limited.
[0349] Example
[0350] Hereinafter, examples will be described, but the present invention is not limited to these examples. In the following description, "parts" and "%" are all based on mass unless otherwise specified.
[0351] <Preparation of Particles>
[0352] -Resin particle dispersion (1)-
[0353] 300 parts by mass of styrene, 11.9 parts by mass of surfactant Dowfax2A1 (47% solution, Dow Chemical Company), and 150 parts by mass of deionized water were mixed and emulsified by stirring at 1,500 rpm for 30 minutes using a dissolver to prepare a monomer emulsion. Next, 0.9 parts by mass of Dowfax2A1 (47% solution, Dow Chemical Company) and 446.8 parts by mass of deionized water were added to a reaction vessel. After heating to 75°C under a nitrogen stream, 24 parts by mass of the monomer emulsion were added. Then, a polymerization initiator solution prepared by dissolving 5.4 parts by mass of ammonium persulfate in 25 parts by mass of deionized water was added dropwise over 10 minutes. After the addition, the mixture was allowed to react for 50 minutes, and then the remaining monomer emulsion was added dropwise over 180 minutes. The mixture was allowed to react for a further 180 minutes, and then cooled to obtain a resin particle dispersion (1). The solid content concentration of the resin particle dispersion (1) was 36.0% by mass. Furthermore, the average particle size of the resin particles was 0.38 μm.
[0354] -Resin particle dispersion (2)-
[0355] 770 parts by mass of styrene, 230 parts by mass of butyl acrylate, 5.0 parts by mass of surfactant Dowfax2A1 (47% solution, Dow Chemical Company), and 576 parts by mass of ion-exchanged water were mixed and emulsified by stirring at 1,500 rpm for 30 minutes using a dissolver to prepare a monomer emulsion. Next, 1,270 parts by mass of ion-exchanged water were added to a reaction vessel. After heating to 75°C under a nitrogen stream, 25 parts by mass of the monomer emulsion were added. Then, a polymerization initiator solution prepared by dissolving 15 parts by mass of ammonium persulfate in 98 parts by mass of ion-exchanged water was added dropwise over 10 minutes. After the addition, the mixture was allowed to react for 50 minutes, and then the remaining monomer emulsion was added dropwise over 220 minutes, and further allowed to react for 50 minutes. Next, a solution prepared by mixing 5 parts by mass of maleic acid and 10 parts by mass of ion-exchanged water was added dropwise over 5 minutes, and after reacting for 150 minutes, the mixture was cooled to obtain a resin particle dispersion (2) which is a dispersion of styrene / acrylic resin particles having acidic groups on the surface. The solid content concentration of the resin particle dispersion (2) was 34.0% by mass, and the average particle size of the resin particles was 0.80 μm.
[0356] <Preparation of Polyimide Precursor-Containing Liquid>
[0357] -Preparation of polyimide precursor-containing liquid (A)-
[0358] 560.0 parts by mass of ion exchange water were heated to 50°C under a nitrogen stream, and 53.75 parts by mass of p-phenylenediamine and 146.25 parts by mass of 3,3',4,4'-biphenyltetracarboxylic dianhydride were added while stirring. A mixture of 150.84 parts by mass of N-methylmorpholine (hereinafter also referred to as "MMO") and 89.16 parts by mass of ion exchange water was added while stirring at 50°C for 20 minutes under a nitrogen stream. By reacting it at 50°C for 15 hours, a polyimide precursor-containing liquid (A) containing 20% by mass of a polyimide precursor in terms of solid content concentration was obtained.
[0359] -Preparation of polyimide precursor-containing liquid (B)-
[0360] 109.06 parts by mass of pyromellitic dianhydride and 100.12 parts by mass of 4,4′-diaminodiphenyl ether were reacted in dimethylacetamide to obtain a polyimide precursor-containing liquid (B) containing 10% by mass of a polyimide precursor in terms of solid content concentration.
[0361] <Example 1>
[0362] 169.85 parts of the polyimide precursor-containing liquid (A), 238.97 parts of the resin particle dispersion (1), and 191.18 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 17.83:173.35) were mixed.
[0363] The mixture was ultrasonically dispersed at 50° C. for 30 minutes to obtain a polyimide precursor solution in which resin particles were dispersed. Then, a porous polyimide film was obtained using the obtained polyimide precursor solution in the following manner.
[0364] A stainless steel substrate with a thickness of 1.0 mm for forming a coating film of a polyimide precursor solution was prepared. The polyimide precursor solution was applied to the stainless steel substrate in an area of 10 cm×10 cm using an applicator so that the film thickness after coating and drying was 400 μm to obtain a coating film. The obtained coating film was heated and dried at 50° C. for 120 minutes (first step).
[0365] Then, the temperature was raised at a rate of 10° C. / min, and the temperature was maintained at 200° C. for 60 minutes, and then the mixture was cooled to room temperature and immersed in tetrahydrofuran for 30 minutes to remove resin particles (second step).
[0366] Next, the temperature was raised from room temperature (25°C, the same below) at a rate of 10°C / min, and when the temperature reached 350°C, it was maintained for 60 minutes (third step).
[0367] Then, the mixture was cooled to room temperature to obtain a porous polyimide membrane having a thickness of 20 μm.
[0368] <Example 2>
[0369] A porous polyimide membrane was obtained in the same manner as in Example 1 except that the drying was performed by heating at 80° C. in the first step and the temperature was maintained at 400° C. for 60 minutes in the third step.
[0370] A cross-sectional photograph of the porous polyimide membrane obtained in Example 2 is shown in Figure 5 .
[0371] <Example 3>
[0372] A porous polyimide membrane was obtained in the same manner as in Example 1, except that the first step was to heat and dry at 80°C, the second step was to keep the temperature at 200°C for 60 minutes and then at 350°C for 60 minutes to remove particles, and the third step was to keep the temperature at 400°C for 60 minutes.
[0373] <Example 4>
[0374] A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1 except that 289.65 parts of a polyimide precursor-containing liquid (A), 172.41 parts of a resin particle dispersion liquid (1), and 137.94 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 30.41:107.53) were mixed. A porous polyimide membrane was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution in which resin particles were dispersed was used.
[0375] <Example 5>
[0376] A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1 except that 289.65 parts of a polyimide precursor-containing liquid (A), 172.41 parts of a resin particle dispersion liquid (1) and 137.94 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 30.41:107.53) were mixed. A porous polyimide membrane was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution in which resin particles were dispersed was dried by heating at 80° C. in the first step and maintained at 400° C. for 60 minutes in the third step.
[0377] <Example 6>
[0378] A polyimide precursor solution containing resin particles was obtained in the same manner as in Example 1 except that 289.65 parts of a polyimide precursor-containing liquid (A), 172.41 parts of a resin particle dispersion liquid (1) and 137.94 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 30.41:107.53) were mixed. A porous polyimide membrane was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution containing resin particles was dried by heating at 80° C. in the first step, the particles were removed after being kept at 200° C. for 10 minutes in the second step, and the temperature was kept at 400° C. for 60 minutes in the third step.
[0379] <Example 7>
[0380] A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1 except that 289.65 parts of a polyimide precursor-containing liquid (A), 172.41 parts of a resin particle dispersion liquid (1) and 137.94 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 30.41:107.53) were mixed. A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution in which resin particles were dispersed was dried by heating at 80°C in the first step, maintained at 200°C for 60 minutes and then maintained at 350°C for 60 minutes in the second step to remove particles by heating, and maintained at 400°C for 60 minutes in the third step to obtain a porous polyimide membrane.
[0381] <Example 8>
[0382] A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1 except that 350.0 parts of a polyimide precursor-containing liquid (A), 147.1 parts of a resin particle dispersion liquid (2) and 102.9 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 36.75:66.15) were mixed. A porous polyimide membrane was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution in which resin particles were dispersed was used.
[0383] <Example 9>
[0384] A polyimide precursor solution containing resin particles was obtained in the same manner as in Example 1 except that 350.0 parts of a polyimide precursor-containing liquid (A), 147.1 parts of a resin particle dispersion liquid (2) and 102.9 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 36.75:66.15) were mixed. A porous polyimide membrane was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution containing resin particles was dried by heating at 80° C. in the first step and maintained at 400° C. for 60 minutes in the third step.
[0385] <Example 10>
[0386] A polyimide precursor solution containing a liquid (A) of 350.0 parts, a resin particle dispersion liquid (2) of 147.1 parts, and an aqueous solvent (a mixed solution of NMP and water, mass ratio = 36.75:66.15) of 102.9 parts was mixed to obtain a polyimide precursor solution containing resin particles dispersed therein in the same manner as in Example 1. A porous polyimide membrane was obtained in the same manner as in Example 1 except that the obtained polyimide precursor solution containing resin particles was dried by heating at 80° C. in the first step, the particles were removed after being kept at 200° C. for 10 minutes in the second step, and the temperature was kept at 400° C. for 60 minutes in the third step.
[0387] A cross-sectional photograph of the porous polyimide membrane obtained in Example 10 is shown in Figure 6 .
[0388] <Example 11>
[0389] A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1 except that 350.0 parts of a polyimide precursor-containing liquid (A), 147.1 parts of a resin particle dispersion liquid (2) and 102.9 parts of an aqueous solvent (a mixed solution of NMP and water, mass ratio = 36.75:66.15) were mixed. A polyimide precursor solution in which resin particles were dispersed was obtained in the same manner as in Example 1, and heat-dried at 80° C. in the first step, and then kept at 200° C. for 60 minutes and then kept at 350° C. for 60 minutes in the second step to remove particles by heating, and kept at 400° C. for 60 minutes in the third step to obtain a porous polyimide membrane in the same manner as in Example 1.
[0390] Various conditions of Examples 1 to 11 are summarized in Table 1 below.
[0391]
[0392] <Comparative Example 1>
[0393] A porous polyimide membrane was obtained in the following manner.
[0394] 0.3 parts by mass of monodispersed spherical particles of silica with a diameter of 400 nm manufactured by NIPPON SHOKUBAI CO., LTD. were dispersed in 10 parts by mass of pure water to prepare a suspension. The suspension was filtered under reduced pressure using a 100 μm membrane filter so that it was most densely packed on the filter with a thickness of 200 μm. Next, the silica was dried, removed from the filter, and calcined at 1100°C for 3 hours. The polyimide precursor-containing liquid (B) was filled on the obtained silica flakes, and the temperature was increased from room temperature to 380°C at a rate of 10°C / min, maintained at 380°C for 1 hour, and then cooled to room temperature. The obtained polyimide membrane containing silica was immersed in a 10% aqueous hydrogen fluoride solution for 12 hours to dissolve and elute the silica, thereby obtaining a porous polyimide membrane with a film thickness of 20 μm.
[0395] <Comparative Example 2>
[0396] A porous polyimide membrane was obtained in the following manner.
[0397] 59.02 parts by mass of the polyimide precursor-containing liquid (B) and 40.98 parts by mass of silica monodisperse spherical particles having a diameter of 600 nm manufactured by NIPPON SHOKUBAI CO., LTD. were mixed and the mixture was ultrasonically dispersed at 50° C. for 30 minutes to obtain a polyimide precursor solution in which silica particles were dispersed.
[0398] The polyimide precursor solution was applied to a stainless steel substrate in an area of 10 cm × 10 cm using an applicator so that the film thickness after coating and drying was 400 μm to obtain a coating film. The obtained coating film was heated and dried at 100°C for 1 hour, and the temperature was raised at a rate of 10°C / min until 380°C. After being kept at 380°C for 1 hour, it was cooled to room temperature. The obtained polyimide film containing silicon dioxide was immersed in a 10% hydrogen fluoride aqueous solution for 12 hours to dissolve and elute the silicon dioxide, thereby obtaining a porous polyimide film with a film thickness of 20 μm. The obtained porous polyimide film was extruded in the thickness direction to obtain a porous polyimide film with a film thickness of 10 μm.
[0399] [Measurement and calculation]
[0400] The average flatness, coefficient of variation of the distance between near pores, porosity, and average major axis of the obtained porous polyimide film were determined by the above-described method.
[0401] The results are shown in Table 2.
[0402] [evaluate]
[0403] (1) Evaluation of tensile strength at break
[0404] The obtained porous polyimide membrane was used to measure the tensile strength at break by the above-mentioned method and evaluated according to the following criteria.
[0405] -Evaluation Criteria-
[0406] A: Tensile strength at break is 30MPa or more
[0407] B: Tensile strength at break is 20 MPa or more and less than 30 MPa
[0408] C: Tensile breaking strength is less than 20MPa
[0409] (2) Evaluation of air permeability
[0410] The obtained porous polyimide membrane was used to prepare a sample for measuring air permeability according to the Gurley method (JIS P 8117:2009). The obtained sample for measuring air permeability was used to measure air permeability by the method described above. The results are shown in Table 2.
[0411] (3) Evaluation of cycle characteristics
[0412] A lithium-ion secondary battery was produced using a porous polyimide film as a separator. The obtained secondary battery was used to investigate the reduction rate of the battery capacity when it was repeatedly charged and discharged 500 times (1C charge and 1C discharge at 25°C). The smaller the reduction rate of the battery capacity, the better the cycle characteristics. The results are shown in Table 2.
[0413] -Evaluation Criteria-
[0414] A: The battery capacity reduction rate is less than 20% (good)
[0415] B: The battery capacity decrease rate is more than 20% (bad)
[0416]
[0417] According to the results shown in Table 2, it can be seen that the porous polyimide membrane obtained in this example has high tensile strength at break and high air permeability.
[0418] In addition, it was found that the porous polyimide membrane obtained in this example also had excellent cycle characteristics.
[0419] The above-mentioned embodiments of the present invention are provided for the purpose of illustration and description. In addition, the embodiments of the present invention do not fully and exhaustively include the present invention, and do not limit the present invention to the disclosed methods. Obviously, various modifications and changes are self-evident to those skilled in the art to which the present invention belongs. The present embodiment is selected and described in order to most easily understand the principles of the present invention and its application. Thus, other technicians in the technical field can understand the present invention by using various modified examples optimized for the determination of the assumed various embodiments. The scope of the present invention is defined by the above claims and their equivalents.
[0420] Explanation of symbols
[0421] 10-resin-based skeleton, 20-cavities, 100-porous polyimide membrane, 200-lithium-ion secondary battery, 300-all-solid-state battery.
Claims
1. A porous polyimide film having a plurality of holes, wherein the average flatness of the plurality of holes is in the range of 0.1 to 0.6, the coefficient of variation of the distance between the holes is in the range of 0.10 to 0.40, and the surface and the back surface are connected through the plurality of holes.
2. The porous polyimide membrane according to claim 1, wherein The average flatness is in the range of 0.2 to 0.
6.
3. The porous polyimide membrane according to claim 1, wherein The porosity of the porous polyimide film is in the range of 45% to 85%.
4. The porous polyimide membrane according to claim 1, wherein The average major diameter of the plurality of holes is in the range of 50 nm to 1500 nm.
5. The porous polyimide membrane according to claim 1, wherein The porous polyimide film has a tensile strength of 20 MPa or more.
6. The porous polyimide membrane according to any one of claims 1 to 5, wherein The air permeability is 300 seconds / 100 mL or less. 7 . A separator for a secondary battery, comprising the porous polyimide film according to claim 6 . 8 . A secondary battery comprising the separator for a secondary battery according to claim 7 .
Citation Information
Patent Citations
Separator for secondary battery and lithium secondary battery using the same
JP2011060539A
Porous film, roll body, and method for producing porous film
JP2017128691A
Laminated non-woven fabric
CN102414016A
Porous polyimide film
JP2003026849A
Porous insulating film and its laminates
US20030129379A1